COUGH AND CHEST PAIN WITH AN UNCOMMON CAUSE - Das, Indrani; Talukdar, Payel; Das, Kalyan; Verma, Sumit; Makhal, Moloy Kanti (Asian Journal of Pharmaceutical and Clinical Research, 2015)
MultipleÂ Hereditary Â ExostosesÂ isÂ anÂ autosomalÂ dominantÂ disorderÂ withÂ multipleÂ cartilageÂ cappedÂ bonyÂ outgrowthsÂ inÂ tibiaÂ ,fibula, femur,Â andÂ sometimesÂ theÂ ribsÂ andÂ scapula. They mayÂ presentÂ withÂ varietyÂ ofÂ symptomsÂ dependingÂ onÂ theÂ structuresÂ it Â compressesÂ suchÂ asÂ nerves,Â arteriesÂ orÂ mayÂ leadÂ toÂ limbÂ deformitiesÂ orÂ mayÂ causeÂ bursitis , orÂ mayÂ undergoÂ malignantÂ transformation. AÂ 33 year oldÂ maleÂ presentedÂ toÂ ourÂ outpatientÂ departmentÂ withÂ recurrentÂ coughÂ andÂ leftÂ sidedÂ chestÂ pain. OnÂ evaluationÂ heÂ wasÂ foundÂ toÂ haveÂ multipleÂ bonyÂ outgrowthsÂ in the scapula ,5thÂ rib , andÂ limbs. SimilarÂ bonyÂ outgrowthsÂ wereÂ alsoÂ presentÂ inÂ hisÂ fatherÂ andÂ grandfather. OnÂ clinicalÂ andÂ radiologicalÂ basisÂ aÂ diagnosis ofÂ MultipleÂ HereditaryÂ ExostosesÂ wasÂ made. HisÂ symptomsÂ graduallyÂ subsidedÂ withÂ removalÂ ofÂ theÂ ribÂ andÂ scapularÂ exostoses. ThusÂ evaluationÂ ofÂ bonyÂ structuresÂ shouldÂ notÂ beÂ overlookedÂ inÂ casesÂ ofÂ coughÂ andÂ chestÂ pain. Keywords: Cough, Chestpain, MultipleÂ HereditaryÂ Exostoses. Â